CULTURAL RELATION ON DISCOURSE MARKERS IN PUNCHLINES ON RICKY GERVAIS’ SUPERNATURE STAND-UP COMEDY SHOW - Azzahra Amalia; Heri Heryono (SAMPURASUN, 2024)
This research investigates the intricate functions of discourse markers (DMs) in Ricky Gervais' stand-up comedy, exploring their alignment with humour theories and their impact on punchline delivery. The purpose of this research is (1) to define the categories and functions of DMs utilised by Ricky Gervais in formulating punchlines and (2) to define the application of DMs in the punchlines within the framework of three theories of humour. The data was obtained from Ricky Gervais’ Stand-up Comedy Show entitled “SuperNature” on Netflix. A qualitative descriptive was applied. The theoretical basis of this research is Brinton’s theory which entails the category and function of DMs and Raskin’s theory regarding the creation of humour. Through examination, the research reveals that Gervais employs a diverse set of DM functions to navigate and enrich his comedic narratives, including the textual and interpersonal categories. The textual category, specifically on DM as an information indicator, indicates the highest overall outcome, with 18%. Moreover, their appearance showcases the dynamic role of DMs in appealing to humour theories. It can be shown that DM commonly appeared in the punchlines on the show, reaching a significant number of 46% in the incongruity category, aiding and amplifying punchlines.